Tafsir Application in the Customs and Rules and Social Behavior of the Various Society - Abrorov, Ilyes Mukhrimhonovich; Sabitova, Siumbel Usmanovna; Khabibullina, Alfiya Marselevna; Yassin, Mohamed Magdy (International Journal of Criminology and Sociology, 2022)
This paper is a description of one of the essential methods used in Qur’anic exegetics: the thematic tafsir method. The authors give a definition of thematic tafsir, trace the history of the origin and development of this method, and also highlight the most critical areas of application of the thematic tafsir. Besides, the paper describes the thematic tafsir as a sensual and rational experience of a believing interpreter of the Qur'an, describes the motivations of a person who decided to resort to this method. The rationale for the thematic tafsir method is also given in terms of Islamic doctrine. In addition, the authors distinguish and describe the three main sections of the thematic tafsir: tafsir of the Qur’anic terms, tafsir of the Qur’anic themes, tafsir of the Qur’anic suras. The authors also write about the developing and expanding areas of application of the thematic tafsir method. Attention is paid to the linguistic direction of the thematic tafsir. The paper also indicates the leading Islamic ulama theologians who successfully apply the method under consideration used in the research. In addition, the contribution to the thematic tafsir of the French scientist Jules La Bohm is emphasized. Among the most popular topics for thematic tafsir, the authors distinguish the following: peace, science, nation, justice, hypocrisy. In conclusion, the authors emphasize the importance of the thematic tafsir for secular and Islamic science and the Islamic community.